Pedigree analysis of glucose-6 phosphate dehydrogenase (G6PD) deficiency of a Javanese Chinese family in Indonesia - IDG Ugrasena; Taku Shirakawa; Kaoru Nishiyama; Masafumi Matsuo (Indonesian Pediatric Society Publishing House, 2017)
The molecular and pedigree analyses in a Javanese Chinese family were carried oul on glucose-6-phosphate dehydrogenase deficiencies. By method of  MPTP scanning without the sequencing steps, those variants could be confirmed. Two out of three sons were clinically jaundiced at birth due to G6PD deficiency and identified to have a G to T nucleotide change al 1376th nucleotide 01 the G6PD gene (GI376T), corresponding to G6PD Canton. Another son was also identified to have a C to T nucleotide change at 1311st nucleotide 01 the G6PD gene (CI311T), corresponding to a Silent mutation. Their father was normal, but their mother obsorved to have the heleromutation 01 G1376T (G6PD Canton and C1311T (a Silent mutation).